2016
DOI: 10.1590/s0100-736x2016000800010
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac markers in five different breeds of rabbits (Oryctolagus cuniculus Linnaeus, 1758) used for cardiovascular research

Abstract: RESUMO.-[Marcadores cardíacos em cinco diferentes raças de coelhos (Oryctolagus cuniculusLinnaeus, 1758) utilizados para pesquisa cardiovascular.] Biomarcadores cardíacos têm sido avaliados em coelhos para avaliação clínica e experimental das doenças cardíacas. Entretanto diferentes testes laboratoriais têm sido utilizados e relatados, sem uma confluência de resultados. Os objetivos deste estudo foram verificar os efeitos de diferentes raças de coelhos sobre as concentrações séricas de ANP, CRP e ACE, além de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
3
0
1
Order By: Relevance
“…All animals in the control group had normal ESR values and slightly elevated CRP values that were significantly lower than osteomyelitis values. 33 , 34 Taken together with the body mass and temperature profiles, these data indicate an early acute phase of the infection, lasting approximately 14 days, followed by a less symptomatic chronic phase. Laboratory values of WBC differentials revealed leukocytosis in the chronic PJI group.…”
Section: Resultsmentioning
confidence: 77%
“…All animals in the control group had normal ESR values and slightly elevated CRP values that were significantly lower than osteomyelitis values. 33 , 34 Taken together with the body mass and temperature profiles, these data indicate an early acute phase of the infection, lasting approximately 14 days, followed by a less symptomatic chronic phase. Laboratory values of WBC differentials revealed leukocytosis in the chronic PJI group.…”
Section: Resultsmentioning
confidence: 77%
“…Há grandes progressos nos estudos sobre os biomarcadores cardíacos, entretanto, não existe atualmente nenhum marcador cardíaco que tenha ganhado lugar no perfil bioquímico da rotina veterinária (ALVES et al, 2015;BOER et al, 2015;FERREIRA et al, 2016;MATTIN et al, 2018), embora os estudos já mostrem os benefícios da sua aplicação clínica na avaliação de pacientes graves, com ou sem doença cardíaca. Atualmente, a avaliação cardíaca na veterinária ainda se faz por meios de ausculta, radiografias, eletrocardiograma (ECG) e ecodopplercardiografia (ECO) (LANGHORN; WILLESEN, 2016; MILLER; JAFFE 2016).…”
Section: Biomarcadores Cardíacosunclassified
“…Most importantly, it is necessary to delay degradation (like hemolysis, for instance) during collection procedures and transportation to a laboratory. Furthermore, samples have to be centrifuged and kept under refrigeration immediately after collection [ 5 , 9 , 31 , 34 - 37 ]. Sample storage methods also greatly influence the values of NT-proBNP in serum.…”
Section: Laboratory Evaluationmentioning
confidence: 99%
“…Research has shown that serum and plasma levels of NT-proBNP in dogs and cats are the only biomarkers that afford to diagnose and monitor congestive processes and, indirectly, assess the myocardial function of small animals [ 2 ]. For this reason, the interest in NT-proBNP in veterinary medicine has grown in the past 10 years, even though it is used mainly in some research contexts because proper methodologies have not been validated and standardized for clinical practice [ 7 - 9 ].…”
Section: Introductionmentioning
confidence: 99%